2017
DOI: 10.1111/myc.12594
|View full text |Cite
|
Sign up to set email alerts
|

Performance of magnetic resonance imaging in pulmonary fungal disease compared to high‐resolution computed tomography

Abstract: To evaluate the performance of magnetic resonance imaging (MRI) compared to computed tomography (CT) in patients diagnosed with pulmonary mycosis. We prospectively included 21 patients diagnosed with pulmonary mycosis between January 2013 and October 2014. Inclusion criteria were presence of respiratory symptoms, histopathological diagnosis of mycosis and absence of mycosis treatment. Reviewers identified one predominant imaging pattern per patient: nodular, reticular or airspace pattern. Afterwards, all CT fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…CT is preferable to MRI in immunocompromised patients with ARI who have normal, equivocal, or nonspecific chest radiographs. CT remains superior to MRI in the detection and characterization of pulmonary parenchymal infection [9,10]. However, MRI can be considered as an alternative imaging modality, albeit less sensitive.…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 99%
“…CT is preferable to MRI in immunocompromised patients with ARI who have normal, equivocal, or nonspecific chest radiographs. CT remains superior to MRI in the detection and characterization of pulmonary parenchymal infection [9,10]. However, MRI can be considered as an alternative imaging modality, albeit less sensitive.…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 99%
“…DWI is a non-invasive MRI technique that is capable of probing the structure of biological tissues at a molecular level and provide information about tumor cellularity and cell membrane integrity. Recent studies have demonstrated the potential of this modality to differentiate malignant from benign pulmonary tissues.MRI is now considered to be an alternative radiation-free method for the evaluation of lung parenchymal diseases and is particularly helpful in children, pregnant women, and young patients requiring multiple follow-up studies [4,[85][86][87].…”
Section: Five-year Viewmentioning
confidence: 99%
“…Lung mycoses are usually self-limited, but some patients develop acute or chronic infection. A high index of suspicion may be required to diagnose fungal infections, particularly for patients who do not reside in endemic areas [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients usually present with fever, cough, hemoptysis, chest tightness, and difficulty breathing. The imaging of fungi is not specific; however, the halo sign and air crescent sign have certain guiding significance in the diagnosis of pulmonary mycosis (8,9). Fungi can destroy host tissue cells and multiply rapidly in bronchial cavities and lung cavities, causing damage to human tissues.…”
Section: Introductionmentioning
confidence: 99%